Design of a chiral molecular pocket in a Ni(II) complex to improve stereoselectivity in the kinetic resolution of racemic epoxides with CO2 - Mikhail A. Emelyanov; Alexander V. Bachinskiy; Yana V. Derkach; Vasiliy A. Chaliy; Alexander F. Smol'yakov; Michael G. Medvedev; Aleksei A. Titov; Victor I. Maleev; Vladimir A. Larionov (Tetrahedron Chem)
The kinetic resolution of racemic epoxides using the carbon dioxide (CO2) molecule is of significant practical interest because the reaction yields the valuable products – enantiomerically enriched cyclic carbonates (1,3-dioxolan-2-ones), along with the remaining opposite enantiomer of the epoxide. However, one is the main challenges in this direction is the absence of the universal and efficient chiral catalytic systems for the resolution of different epoxides by CO2 with a high selectivity factor (s). In this context, we herein present a perspective proof-of-concept approach for the improvement of stereoselectivity in the resolution of terminal epoxides by a rational design of an appropriate chiral molecular pocket in a Ni(II) complex based on commercially available (S)-(2-aminomethyl)pyrrolidine and 3,5-di-tert-butylsalicylaldehyde. The obtained chiral Ni(II) complex with iodide-anion catalyzes the kinetic resolution of epoxides by CO2 with s-factor up to 7.8, while the addition of a suitable chiral ligand to this system, particularly, (S)-(2-anilinomethyl)pyrrolidine led to the increasing of s-factor up to 11.5 in the case of challenging styrene oxide (ee of styrene cyclic carbonate was 82%) which is being one of the best results for this substrate to date. It is gratifying to note that even achiral co-ligands can be used, greatly simplifying the catalytic system. The experimental and spectral data and DFT calculations revealed the mechanism of catalysis and enantioselection.